The Use of Antibody-sensitized Latex to detect Cymbidium Mosaic Virus in Orchids - Abdul Samad, Norani; Ari, Zainab (Universiti Putra Malaysia Press, 1993)
Latex agglutination test (L) and a modification of the latex test, protein A-coated latex (PAL) were compared for sensitization with antibodies to Cymbidium mosaic virus (CyMV). A series of globulin concentrations was tested against purified CyMV. The minimum detectable virus concentration was similar for both L and PAL reactions at 0.104 llg/ml. The detectable end points in infected Oncidium Gower Ramsey orchid sap were similar at a dilution of 1/2560. PAL was found to be more sensitive than L at a higher globulin dilution of 1/512. The PAL test showed higher sensitivity than L based on five orchid hybrids and compared favourably with electron microscopy test.